Metaverse technology tree: a holistic view - Ghazinoory, Sepehr; Parvin, Fatemeh; Saghafi, Fatemeh; Afshari-Mofrad, Masoud; Ghazavi, Nafiseh; Fatemi, Mehdi (Frontiers in Artificial Intelligence, 2025)
IntroductionThe Metaverse has emerged as a significant trend in recent years, offering solutions across diverse fields. Despite substantial investments and extensive research efforts, a comprehensive understanding of the Metaverse environment and its full potential remains elusive. This article seeks to address this gap by developing a technology tree for the Metaverse based on published standards, prior studies, and frameworks proposed by leading firms.MethodsTo construct the Metaverse technology tree, a systematic literature review approach was employed. From an initial pool of 354 scientific papers, conference proceedings, book chapters, and reports, a rigorous screening process –focused on titles, abstracts, and full-texts –resulted in a selection of 81 final sources. These sources were synthesized using a meta-analysis methodology.ResultsThe meta-synthesis of the selected literature produced a comprehensive Metaverse technology tree encompassing seven key branches: artificial intelligence, Mirror World, extended reality, network infrastructure, lifelogging, blockchain, and the Internet of Things. Each branch represents a critical technological area necessary for the development and realization of the Metaverse.DiscussionThe proposed Metaverse technology tree offers a holistic overview and roadmap of the technological domains underlying the Metaverse. By identifying these seven branches, this research provides valuable guidance for future studies and development trajectories in Metaverse technologies.